Challenging boundaries to cross: primary teachers exploring drama pedagogy for creative writing with theatre educators in the landscape of performativity. Issue 2 (14th March 2020) - Dobson, Tom; Stephenson, Lisa
ABSTRACT: This paper focuses on the professional development of primary school teachers using drama to develop creative writing across the curriculum. Sponsored by the United Kingdom Literacy Association, the two-term project involved four teachers working with theatre educators to use process drama. The collaborative approach was supported by learning conversations, which took place after each lesson, involving Higher Education academics. Data were collected by academics observing the lessons, taking notes during learning conversations and undertaking interviews with the teachers in order to capture experiences of the landscape of education as they were encouraged to cross boundaries of practice. Data were analysed using Clarke's model (2009) of teacher identity and this demonstrates how three of the four teachers resisted boundary crossing as a result of the landscape of performativity, which is seen to prohibit child-centred approaches. One teacher was able to cross boundaries and this is seen to be a result of the substance and telos of his identity. His boundary crossing emphasised the theatre educators' reluctance to change their self practices – the paper concludes by highlighting the importance of all partners being involved in practice, learning conversations and data collection in order to create the ideal conditions for boundary crossing.